INCLUSION OF THE RUSSIAN HIGHER EDUCATION SYSTEM INTO THE EUROPEAN HIGHER EDUCATION AREA - Elena V. Guslyakova; Artur L. Demchuk; Irina G. Teleshova (Moscow Polytechnic University, 2016)
The article highlights the main factors affecting the inclusion of the Russian higher education system into the European Higher Education Area focusing onthe preparation of the Russian Federation National Report for the upcoming EHEA Ministerial Conference(that will take place in Yerevan, Armenia in 2015) which is carried out within the framework of the project "Expert and analytical support of the inclusion of the Russian higher education system into European Higher Education Area withdue consideration of the European practice of integration of education and labor market and of the network form of educational programs" of the Federal Target Program for the Development of Education in 2011-2015.The article presents an information about methodological and information analysis network Centre established atthe Faculty of Economics, Lomonosov Moscow State University for the development of mechanismsof implementation and dissemination of the best practices of higher education institutions, for organizing training events, consultations and dissemination of the experience on various issues of the inclusion of the Russian higher education system into European Higher Education Area.